The effect of head protection on the hearing of rugby players. Issue 9 (9th September 2008) - Kieran, S M; Dunne, J; Hughes, J P; Fenton, J E
Abstract : Objective: Professional rugby players utilise various methods of head protection to prevent against the development of a pinna haematoma. This study tests the hypothesis that these measures, whilst preventing injury, decrease the wearers' hearing threshold and therefore their performance. Design and participants: Eight patients had free field audiometry performed in a soundproof room, with warble tones. All patients were young men (mean 24.75 years (range 22–34)). No participant had ear symptomatology or a past history of ear surgery. Three separate audiological assessments were performed on each patient: normal free field audiometry in a sound field room, following application of adhesive tape and whilst wearing a scrum cap. All measurements were performed by a single audiological scientist. A significant clinical drop in hearing threshold was defined as an increase of 10 dB. Results: No patient demonstrated a significant drop in hearing threshold following the application of either tape or a scrum cap, nor was there a significant difference in the mean (SD) warble tone average: air 7.03 (5.47); tape 7.19 (6.40); scrum cap 6.56 (5.58). Conclusion: Theoretical concerns that "ear taping" and scrum caps affect hearing of rugby players are unfounded and should not discourage their use.